Studies on Ironus Bastian, 1865 (Enoplida: Ironidae) from Iran with a comment on its phylogenetic position - Shokoohi, E.; Abolafia, J.; Mehrabi-Nasab, A. (Nematology, 2013)
During a survey on the soil nematodes from Kerman province, three species of Ironus, i.e., I. andamanus, I. elegans and I. ignavus, were isolated from natural areas in Kerman province (Iran). Descriptions, measurements and illustrations are provided for all three species. Furthermore, sequence data of the 18S rDNA gene are provided for I. andamanus and I. elegans. The Blast search results of I. andamanus showed six nucleotide differences with I. longicaudatus (FJ040495) from The Netherlands. Molecular analysis of I. elegans set this population apart from other species of Ironus, although I. elegans is closer to an undescribed Ironus (FJ040496) from The Netherlands. These are the first data of 18S rDNA for I. andamanus and I. elegans. Phylogenetic relationships with other related species of Ironus and closely related genera available in GenBank are discussed.